Effect of soil types on root infection of Acacia mangium and Eucalyptus pellita by Ganoderma philippii and Pyrrhoderma noxium - HERU INDRAYADI; MORAG GLEN; FAHRIZAWATI FAHRIZAWATI; BAYO ALHUSAERI SIREGAR; ANTO RIMBAWANTO; MARDAI MARDAI; BUDI TJAHJONO; CAROLINE MOHAMMED (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Indrayadi H, Glen M, Fahrizawati, Siregar BA, Rimbawanto A, Mardai, Tjahjono B, Mohammed C. 2023. Effect of soil types on root infection of Acacia mangium and Eucalyptus pellita by Ganoderma philippii and Pyrrhoderma noxium. Biodiversitas 24: 2358-2364. Acacia mangium Willd. and Eucalyptus pellita F.Muell. are susceptible to red root-rot disease, caused by Ganoderma philippii (Bres. & Henn. ex Sacc.) Bres., has led to the demise of planted A. mangium as a commercial pulpwood in Indonesia. A second root-rot pathogen, Pyrrhoderma noxium (Corner) L.W.Zhou & Y.C.Dai (syn. Phellinus noxius (Corner) G.Cunn.), also attacks both species. The objective of this study was to investigate the effect of different soil types on the root infection of A. mangium and E. pellita by G. philippii and P. noxium. The effect of three contrasting soil types (mineral R41, R51 and peat soil) used in a plantation estate in Riau province on disease development was investigated in a pot trial using four isolates, two of G. philippii and two of P. noxium. Two models of inoculation were used, in one of which inoculated wood blocks were placed against the seedling roots (Model 1), the second where the blocks were 10-20 cm from the roots (Model 2). Fifty weeks after the experiment was established, mortality was significantly higher in the soil of low than high clay content, in A. mangium than E. pellita, and in Model 1 than Model 2; there was no difference between the two G. philippii isolates, and P. noxium did not cause any mortality. G. philippii inoculum could survive in all three soil types for over 9 months; hence, the effect of soil type was not mediated by inoculum longevity. Alternatives should be pursued to limit further development of root-rot diseases in existing E. pellita estates.